Cardiac T1 mapping enables risk prediction of LV dysfunction after surgery for aortic regurgitation - Sinn, Martin; Petersen, Johannes; Lenz, Alexander; von Stumm, Maria; Sequeira Groß, Tatiana Maria; Huber, Lukas; Reichenspurner, Hermann; Adam, Gerhard; Lund, Gunnar; Bannas, Peter; Girdauskas, Evaldas (Frontiers in Cardiovascular Medicine, 2023)
Background To assess whether cardiac T1 mapping for detecting myocardial fibrosis enables preoperative identification of patients at risk for early left ventricular dysfunction after surgery of aortic regurgitation. Methods 1.5 Tesla cardiac magnetic resonance imaging was performed in 40 consecutive aortic regurgitation patients before aortic valve surgery. Native and post-contrast T1 mapping was performed using a modified Look-Locker inversion-recovery sequence. Serial echocardiography was performed at baseline and 8 ± 5 days after aortic valve surgery to quantify LV dysfunction. Receiver operating characteristic analysis was performed to determine the diagnostic accuracy of native T1 mapping and extracellular volume for predicting postoperative LV ejection fraction decrease >−10% after aortic valve surgery. Results Native T1 was significantly increased in patients with a postoperatively decreased LVEF (n = 15) vs. patients with a preserved postoperative LV ejection fraction (n = 25) (i.e., 1,071 ± 67 ms vs. 1,019 ± 33 ms, p = .001). Extracellular volume was not significantly different between patients with preserved vs. decreased postoperative LV ejection fraction. With a cutoff-of value of 1,053 ms, native T1 yielded an area under the curve (AUC) of .820 (95% CI: .683–.958) for differentiating between patients with preserved vs. reduced LV ejection fraction with 70% sensitivity and 84% specificity. Conclusion Increased preoperative native T1 is associated with a significantly higher risk of systolic LV dysfunction early after aortic valve surgery in aortic regurgitation patients. Native T1 could be a promising tool to optimize the timing of aortic valve surgery in patients with aortic regurgitation to prevent early postoperative LV dysfunction.